Binaphthyl-based chiral ligands: design, synthesis and evaluation of their performance in enantioselective addition of diethylzinc to aromatic aldehydes. Issue 47 (25th November 2020) - Yao, Chao; Wu, Piao; Huang, Yue; Chen, Yaoqi; Li, Lin; Li, Yue-Ming
Abstract : The design strategy and the performance of binaphthyl-based chiral ligands were evaluated with computation and enantioselective addition of diethylzinc to aromatic aldehydes. Abstract : The design strategy and the performance of binaphthyl-based chiral ligands were evaluated with computation and enantioselective addition of diethylzinc to aromatic aldehydes. Under optimized conditions, enantioselective addition of diethylzinc to aromatic aldehydes provided the desired optically active secondary alcohols in high isolated yields (up to 91%) and excellent enantiomeric excesses (up to 98% ee).